Novel Adenosine Deaminase 2 (ADA2) Mutations Associated With Hematological Manifestations - Reem Albalawi MSc (SAGE Publishing, 2021)
Recent progress in laboratory techniques, particularly, identification of novel disease-causing genes, has led to the detection of different gene mutations that might be implicated in the pathogenesis of different hematological disorders like pure red cell aplasia (PRCA) and neutropenia. An autoinflammatory disorder known as deficiency of adenosine deaminase 2 (DADA2) has been recently noticed to present with variable hematologic abnormalities. We report 2 patients who presented with hematologic abnormalities in which 2 ADA2 gene mutations were detected. The first case is a 5-year-old girl who presented with severe PRCA and autoimmune hemolytic anemia without any other manifestation of DADA2 that resulted from a novel CECR1 c.714_738dup, p. (Ala247Glnfs*16) homozygous variant. The second case is a 10-year-old boy, known to have Hodgkin lymphoma and was under follow-up for 6 years; he presented with persistent neutropenia and was discovered to be homozygous for ADA2 c.1447_1451del, p. (Ser483Profs*5). In conclusion, we report two different novels ADA2 variants in two children; the first presented with PRCA and the second presented with persistent neutropenia. This report aims to raise the concerns regarding the use of genetic testing in different hematologic diseases with indefinite etiology, as it will lead to the best therapeutic strategies without the need for unnecessary interventions.